Application of waterborne acrylic emulsions in coated controlled release fertilizer using reacted layer technology - Shen, Yazhen; Zhao, Cong; Zhou, Jianmin; Du, Changwen (Chinese journal of chemical engineering, 2015)
Waterborne acrylic emulsions modified with organic siloxanes and aziridine crosslinker were synthesized and applied as coating of controlled release fertilizer. The free films were characterized and the nutrient release profiles of the coated fertilizers were determined. The results show that methyl silicone oil and methylsilanolate sodium could not improve water resistance performance and glass transition temperature Tgof coatings, while the firmness is enhanced. Aziridine crosslinker improves the water resistance performance, firmness and Tg. Incorporation of methyl silicone oil and aziridine crosslinker gives an excellent aqueous acrylic emulsion for coated controlled release fertilizer, with the 30-day cumulative nutrient release reduced to 16% and an estimated nutrient release duration over 190 days. Therefore, this waterborne coating is promising to meet the requirements for controlled release of nutrient and environmental protection.